Muslim consumers’ awareness towards halal logo on food product in Kota Kinabalu / Nurul Ain Sumpin & Nur Faiezah Kassim - Sumpin, Nurul Ain; Kassim, Nur Faiezah (Faculty of Hotel and Tourism, 2017)
Recently the great demand of Halal food in Malaysia become attention, transform from an exclusive niche market to dynamic global market phenomenon. Malaysia became the first in the world’s Halal food industry where Halal certification been recognized globally by international bodies. Traditionally, Halal is referring to meat and poultry but now it encompasses the whole “from farm to fork”. Halal certification has also developed as a significant force in the Muslim-minority countries, where Halal food has become a defining element of Muslim identity. The introduction of Halal logo issued by JAKIM has influence the awareness and perception among Muslims consumer about the importance of consuming Halal products that follow Shariah law and the important of Halal logo. Objectives of this study are to investigate the awareness of Muslim consumers can recognize Halal logo issued by JAKIM, their familiarity on International Halal logo and awareness towards Halal logo certified by JAKIM. Respondents in this study are Muslim consumer in Kota Kinabalu, Sabah. Structured questionnaire will be distributed to respondents and descriptive analysis to analyses the data. The findings shown that not all the respondent were able to recognize JAKIM Halal logo due to the existence multiple Halal logo in the market. Meanwhile, their familiarity on international Halal logo are depend on the certain country such as Indonesia and Thailand as these two was among the highest country imported food product in Malaysia. Awareness towards Halal logo certified by JAKIM consumer was relying on list of ingredient in evaluating the “Halalness” of the food product. These indicate that the consumers become more cautious and aware to Halal issue as a response to their way of living as a Muslim with knowledge on the concept of Halal.